PENGARUH GOOD CORPORATE GOVERNANCE DAN CORPORATE SOCIAL RESPONSIBILITY TERHADAP NILAI PERUSAHAAN DENGAN KINERJA KEUANGAN DAN SUSTAINABILITY REPORT SEBAGAI VARIABEL INTERVENING PADA INDUSTRI PERBANKAN YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE TAHUN 2013 - 2015 - Nugraha, Made Yoga Putra; Hwihanus, Hwihanus (Universitas 17 Agustus 1945 Surabaya, 2019)
ABSTRACTThis study aims to analyze and explain the relationship between variables of Good Corporate Governance, Corporate Social Responsibility, Financial Performance, Sustainability Reports, value of the firms listed on the Indonesia Stock Exchange. The sample used in this study was a purposive random sampling of 20 companies from 60 conventional commercial bank companies listed on the Indonesia Stock Exchange in 2013-2015. The analysis technique uses partial least square for inner models, outer models, and weight relations. The results of this study indicate that Good Corporate Governance has a significant effect on financial performance, Good Corporate Governance has no significant effect on Sustainability Reports, Corporate Social Responsibility has a significant effect on financial performance, Corporate Social Responsibility has no significant effect on Sustainability Reports, financial performance has a significant effect on firm value, Sustainability Report has no significant effect on company value, Good Corporate Governance has a significant effect on company value, Corporate Social Responsibility has a significant effect on company value, the effect of financial performance has no significant effect on the Sustainability Report. Financial performance and Sustainability Report become intervening variables to the value of the company. Keywords: Good Corporate Governance, Corporate Social Responsibility, Financial Performance, Sustainability Report, Value of the Firm